Early detection of oral health status and cardiometabolic risk factors among reproductive-aged women in rural areas: A cross-sectional study. (1st August 2017) - Ma, Yen-Ying; Huang, Tung-Jung; Lin, Ming-Shyan; Chen, Po-Han; Chen, Mei-Yen
Abstract: Background: Oral health status is associated with many chronic ailments, including diseases of the cardiovascular system, diabetes, as well as pregnancy complications, such as low birth weight, preterm delivery, preeclampsia, and early pregnancy loss. The health status of reproductive-aged women is important, not only for the women themselves, but also for the health of fetus. Objectives: The purpose of this study was to explore cardiometabolic risk factors, oral health status, and associated factors among reproductive-aged women. Methods: The current study is a preliminary report from a nurse-led longitudinal study, examining a health promotion program for women in a rural region of Taiwan. Participants consisted of a community-based, cross-sectional sample, involving 2547 women aged 20–49 years. Results: A high percentage of participants were found to have cardiometabolic risk factors. More than one-quarter had ⩽24 remaining teeth. Many participants reported that they did not regularly attend dental checkups and tooth scaling, did not brush at least twice a day after meals, did not have a healthy diet, and did not exercise regularly. The results also indicated that women with <20 remaining teeth tended to be older, engaged in substance use, and displayed increased cardiometabolic risk factors. Conclusions: The findings indicate that reproductive-aged women show a high prevalence of tooth loss, cardiometabolic risk factors, and unhealthy habits. Nurses in the primary health sectors could reduce the consequences of these risk factors and improve oral health through the early detection and initiation of health-promoting programs that reduce risky behavior associated with cardiometabolic diseases.